A STUDY ON OUTBREAK OF COVID‐19 PANDEMIC FINANCAIL PERFORMANCE OF SELECT BANKS IN BANGALORE - Mubeen, Samiya (International Journal of Psychosocial Rehabilitation, 2020)
Indian banking sector plays a vital role in development of the Indian economy. In 2019 where COVID-19 outbreak has challenged entire world it has an impact on the Indian Banking sector also. Reserve Bank of India (RBI) states that , India’s banking sector is sufficiently capitalised and well-regulated. Credit, market and liquidity risk studies suggest that Indian banks are generally resilient and have withstood the global downturn well. In the Pandemic Indian banking industry has recently witnessed lot of innovative banking models like payments and small finance banks. On the other hand few banks are facing the challenges on recovery of the NPAs, Credit recovery that has a impact on the Profits of the banks. This present study is made to an attempt the impact of NPAs, Credit recovery with Profitability in the pandemic situation in select Banks in Bangalore. For the study, five Indian Banks in Bangalore has taken i.e. Kotak Mahindra Bank, ICICI Bank, HDFC Bank, Axis Bank and YES Bank for a period of 3 years from 2019-20 to 2021-22. The data was analysed using statistical tools like correlation coefficient and graphical representation has been done to evaluate the data.